2021
DOI: 10.1016/j.amjmed.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Basis and Rationale for Early Outpatient Treatment of SARS-CoV-2 (COVID-19) Infection

Abstract: Approximately 9 months of the severe acute respiratory syndrome coronavius-2 (SARS-CoV-2 [COVID-19]) spreading across the globe has led to widespread COVID-19 acute hospitalizations and death. The rapidity and highly communicable nature of the SARS-CoV-2 outbreak has hampered the design and execution of definitive randomized, controlled trials of therapy outside of the clinic or hospital. In the absence of clinical trial results, physicians must use what has been learned about the pathophysiology of SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
145
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(165 citation statements)
references
References 44 publications
(32 reference statements)
1
145
0
4
Order By: Relevance
“…This is in line with the observations that the difference in the viral load decrease was largest between day 1 and day 2 and that the 50% logarithmic reduction in viral load by day 6 was numerically greater in the early treatment group, suggesting the presence of modest antiviral activity in this setting. It has been suggested that antiviral therapy may be more efficacious if given early in the course of COVID-19 on October 30, 2020 by guest http://aac.asm.org/ Downloaded from than that in the terminal stage of illness (7). Favipiravir, which is active in vitro against SARS-CoV-2 and can be administered orally, is an agent which may fit this paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the observations that the difference in the viral load decrease was largest between day 1 and day 2 and that the 50% logarithmic reduction in viral load by day 6 was numerically greater in the early treatment group, suggesting the presence of modest antiviral activity in this setting. It has been suggested that antiviral therapy may be more efficacious if given early in the course of COVID-19 on October 30, 2020 by guest http://aac.asm.org/ Downloaded from than that in the terminal stage of illness (7). Favipiravir, which is active in vitro against SARS-CoV-2 and can be administered orally, is an agent which may fit this paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…The study of 8075 patients in Belgium [ 5 ], 3451 patients in Italy [ 6 ] and 890 European patients with cancer [ 7 ] report clear benefits of chloroquine derivatives on mortality. Contrary to the authors' conclusions, the careful and updated analysis of the literature shows that hydroxychloroquine, particularly when associated with azithromycin, remains one of the best options to date in the treatment of COVID-19 [ 8 ].…”
mentioning
confidence: 99%
“…However, there are some categories with specific risk for unfavorable disease course. The importance of correctly identifying risk groups derives from the need to initiate appropriate treatment in a timely manner, as early treatment may lessen the risk of hospitalization and death [ 2 ].…”
Section: Is There a Specific Category Of Patients Prone To Viral Cmentioning
confidence: 99%